EVALUASI KEBIJAKAN PROGRAM KAMPUS MENGAJAR ANGKATAN 3 DI SD NEGERI TUMBREP 01 - Haniyuhana, Ananda; Katerina Bataha (Jurnal Pendidikan Dasar, 2022)
Kampus Mengajar is one of the public policy products launched by the Directorate of Learning and Student Affaira of Indonesia Ministry of Education and Culture. This program aims to provide opportunities for students to be able to hone their leadership spirit, character and have teaching and learning experiences. It is hoped that the kampus mengajar program can increase the effectiveness of the learning process during the Covid-19 pandemic. The purpose of this study was to describe and analyze the evaluation of numeracy and literacy education through the Kampus Mengajar batch 3 at SD Negeri Tumbrep 01. The type of research used was descriptive with a qualitative approach. This research use CIPP evaluation method (Context, Input, Process, and Product). The results of the evaluation using CIPP method, there are still several obstacles that must be resolved for the success of the next generation of Kampus Mengajar programs. These obstacles include the limitations of teaching staff and infrastructure and the lack of awareness of students and student parent in helping the successful implementation of the kampus mengajar batch 3 at SD Negeri Tumbrep 01.